Auxiliary TARP Subunits Define AMPA Receptor Pharmacology and Function - Bdir, Sosana; Capan, Irfan; Hawash, Mohammed; Servi, Suleyman; Qneibi, Mohammad (Mdpi, 2026)
Background: Fast excitatory transmission in the central nervous system is carried out by AMPA-type glutamate receptors. Neuronal hyperexcitability and epilepsy have been associated with the dysregulation of AMPA receptor function. Modulation of the gating kinetics of AMPA receptor function has been proposed to be a desirable target for therapy, especially when the modulation is transmembrane AMPA receptor regulatory protein (TARP)-dependent and AMPA receptor subunit composition-dependent. Methods: Eight dibenzobarrelene-based heterocycles were characterized for their effects on the human embryonic kidney cells expressing homomeric GluA1 and heteromeric GluA1/2 AMPA receptors, either alone or co-expressed with the TARP gamma 8 auxiliary subunit, using whole-cell patch-clamp electrophysiological recordings, and the current amplitude and kinetics of desensitization and deactivation were measured after rapid glutamate application. Results: Each chemical evaluated suppressed glutamate-induced currents via AMPA receptors and augmented both desensitization and deactivation, indicating a negative allosteric modulatory effect. The co-expression of TARP gamma 8 diminished, but did not eradicate, the inhibition and acceleration induced by the compounds. The observations indicate that the chemicals diminish agonist-bound open states and facilitate transitions to non-conducting states while maintaining effectiveness. Conclusions: The present study describes a specific kinetic mechanism by which dibenzobarrelene derivatives impair the function of the AMPA receptor and its dependence on auxiliary proteins. The present study provides a mechanistic understanding of AMPA receptor gating modulation and establishes a pharmacological framework for future investigations in more physiologically relevant systems.
Keywords: AMPA receptor; GluA1; GluA1/2; TARP gamma 8; dibenzobarrelene